An animated pedagogical agent for learning introduction to object oriented programming concept / Adib Sarkawi - Sarkawi, Adib (2008)
Animated pedagogical agents or APA are animated characters that encourage interactive learning environment (in response to student's or user's actions). Additionally, the agents also play powerful motivational roles as they interact with students. In this project, a multimedia learning application with animated pedagogical agents called OOP - Concept has been developed, where it is able to provide high motivational support for the student, particularly in learning Introduction to Object Oriented Programming Concept. Besides that, evaluations of the application usability (questionnaires and interviews) were also carried out, where levels of the users' satisfactions towards OOP - Concept were identified. The samples involved were 30 Object Oriented Programming I (CSC175) students of University of Mara Technology, Sarawak campus. Notably, the study revealed that the presence of the appealing animated pedagogical agents has produced strong positive effects on the students' perceptions in their learning experiences. The study has also illustrated that most of the students were more motivated and interested to interact with the application as it was equipped with the animated pedagogical agents.